2022
DOI: 10.1002/14651858.cd012026.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving health literacy in people with chronic kidney disease

Abstract: Interventions for improving health literacy in people with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 279 publications
0
6
0
Order By: Relevance
“…A growing literature in the developing field of health literacy continues to demonstrate the effectiveness of interventions regarding behaviours that can ultimately decrease disease burden [ 48 , 49 ]. However, two recently published systematic literature reviews highlighted that the proportion of studies reporting on interventions aimed at improving health literacy in chronic conditions remains low, despite a rapid increase in the number of publications on this health determinant [ 50 , 51 ]. Since health literacy is a multifaceted and complex issue, a global approach may be necessary to effectively tackle its many challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature in the developing field of health literacy continues to demonstrate the effectiveness of interventions regarding behaviours that can ultimately decrease disease burden [ 48 , 49 ]. However, two recently published systematic literature reviews highlighted that the proportion of studies reporting on interventions aimed at improving health literacy in chronic conditions remains low, despite a rapid increase in the number of publications on this health determinant [ 50 , 51 ]. Since health literacy is a multifaceted and complex issue, a global approach may be necessary to effectively tackle its many challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Effective interventions to enhance health literacy to achieve better outcomes in chronic kidney disease management are very broad and include educational interventions, self-management interventions and educational with self-management interventions. However, the review reported a lack of studies targeting a population with poor health literacy [35] Further research into interventions aimed at older adults with low health literacy and hemodialysis are needed. Some limitations should be considered such as a cross-sectional design, a convenience sample, and selfreport for measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy interventions aimed at improving patients’ self-management knowledge and ability could be incredibly useful in patients with CKD at both the early and end stages. A Cochrane systematic review protocol suggested that health literacy interventions aim to mitigate the effects of low health literacy; facilitate literacy skill building; and improve knowledge about disease and treatment, self-care, and comprehension skills [ 10 ].…”
Section: Introductionmentioning
confidence: 99%